Host country concerns and policies toward state-owned MNEs - Alvaro Cuervo-Cazurra (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Different concerns about FDI by state-owned enterprises require separate policies: national security concerns can be dealt by exclusion of all foreign investors; worries about the opacity of foreign SOEs can be solved via monitoring; and unease about adversarial governments' SOEs can be reduced using controls.
Keywords: 330